2006
DOI: 10.1243/09544054jem651
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for best practice knowledge management

Abstract: Capturing and reusing knowledge of best practices has been identified as one of the requirements for next-generation product development. Knowledge identification is therefore already being done to some degree in many organizations, through instruction manuals or 'how to' guidelines. However, this is only a first step, as to fully exploit valuable knowledge, best practices must be identified and shared. A detailed review of previous research in best practice knowledge management shows that the method of modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 22 publications
0
17
0
3
Order By: Relevance
“…It involves the systematic identification, measurement, and benchmarking of processes that result in better outcomes (Watson, 1993). Dani et al (2006) noted that what is meant by 'best' are those practices that have been shown to produce superior results; selected by as systematic process; and judged as exemplary, good, or successfully demonstrated (p. 1718). Benchmarking is a way to search for practices that lead to superior performance (Camp, 1989;Lankford, 2000) and of adopting best practices (Dani et al, 2006;Paauwe & Boselie, 2005).…”
Section: Theoretical Underpinnings Of the Family Business Best Practimentioning
confidence: 99%
See 1 more Smart Citation
“…It involves the systematic identification, measurement, and benchmarking of processes that result in better outcomes (Watson, 1993). Dani et al (2006) noted that what is meant by 'best' are those practices that have been shown to produce superior results; selected by as systematic process; and judged as exemplary, good, or successfully demonstrated (p. 1718). Benchmarking is a way to search for practices that lead to superior performance (Camp, 1989;Lankford, 2000) and of adopting best practices (Dani et al, 2006;Paauwe & Boselie, 2005).…”
Section: Theoretical Underpinnings Of the Family Business Best Practimentioning
confidence: 99%
“…The best practice approach to business performance and excellence has been critiqued along several grounds including: Practices need to be context specific and prioritized (Purcell, 1999); relationship between best practices and performance (Davies & Kochhar, 2000); adoption of best practices is insufficient to emulate success of key players (Szulanski, 1996); challenges in selecting and applying best practices (Brannan, Durose, John, & Wolman, 2008); loss of meaning resulting from increased use of best practice terminology (Dani et al, 2006;Patton, 2001); better practices rather than best (Patton, 2001;Smith & Sutton, 1999).…”
Section: A Critique Of the Best Practice Approachmentioning
confidence: 99%
“…A good lector should use this fact to activate other participants and to provide such an erudite professional the chance to contribute as a way of refreshing and improving the quality of instruction. (Dani, Harding, Case, Young, Cochrane, Gao & Baxter, 2006). In evaluating the results of instruction, the following should be adhered to:…”
Section: Implementation and Control Of An Educational Programmentioning
confidence: 99%
“…Now, individuals who share common interests can meet virtually in an online community without geographical restriction [8]. The great majority of virtual communities depend on Web-based environments to connect, collaborate, communicate and contribute to community activities [9,10]. A community's specific purpose and goals inform the appropriate activities and technologies that should support it.…”
Section: Introductionmentioning
confidence: 99%